Alpha-lipoic acid regulates pro-inflammatory cytokines and hormones in letrozole-induced polycystic ovary syndrome in rats - Fehintoluwa Joy Femi-Olabisi; Olawunmi Rashidat Oyerinde; Opeyemi Olubunmi Faokunla; Sikemi Adejoke Omar; Precious Evy Igene; Olamide Esther Asaluwala; Bisi Olajumoke Adeoye; Odunayo Olowolehin Oladoye (Endocrine and Metabolic Science)
Polycystic ovary syndrome (PCOS) a common endocrine disorder affecting 5–10 % of women in their reproductive age with reproductive and metabolic disorders such as anovulation/oligo-ovulation, hyperinsulinemia, glucose intolerance, obesity and dyslipidemia. Among other heterogeneous symptoms, studies have linked PCOS to low-grade chronic inflammation. Alpha-lipoic acid (ALA), an essential mitochondrial co-factor and safe natural molecule acts as an antioxidant. In this study, letrozole-induced PCOS rat model was used to investigate the effect of ALA on inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and hormones such as testosterone (T), luteinizing hormone (LH) and insulin. Twenty-eight rats were randomly divided into four groups of seven rats each- Group 1,2,3 and 4 (Control, PCOS, PCOS+metformin (MET) + clomiphene citrate (CC), and PCOS+ALA respectively). PCOS was induced by orally administering 1 mg/kg/day of letrozole for 21 days. ALA (1 mg/day) was administered orally to PCOS rats, and the reference drugs (7.14 mg/kg/day of MET co-administered with 2 mg/kg/day CC) were given orally for 14 days. Results revealed acyclicity in the oestrous cycle of PCOS rats characterized by persistent estrus and diestrus phases was completely reversed by ALA compared to the reference drug-treated PCOS group. ALA decreased serum fasting blood sugar, IL-6, TNF-α, total cholesterol (TC), Triglycerides (trigs), low-density lipoprotein-cholesterol (LDL-C), insulin, and LH. Serum high-density lipoprotein-cholesterol (HDLC) was significantly increased (p < 0.05) in the ALA-treated group compared to the control rats. Therefore, the efficacy of ALA as a regulator of pro-inflammatory cytokines and reproductive factors can be exploited in developing treatments for PCOS.